Current progress and future perspectives of neoadjuvant anti-PD-1/PD-L1 therapy for colorectal cancer - Zhengyang Yang; Guocong Wu; Xiao Zhang; Jiale Gao; Cong Meng; Yishan Liu; Qi Wei; Liting Sun; Pengyu Wei; Zhigang Bai; Hongwei Yao; Zhongtao Zhang (Frontiers in Immunology, 2022)
Immunotherapies, especially the programmed cell death 1/programmed cell death ligand 1 (PD-1/PD-L1) inhibitors, have revolutionized the therapeutic strategies of various cancers. As for colorectal cancer (CRC), the current clinical application of PD-1/PD-L1 inhibitors are mainly used according to the mutation pattern, which is categorized into deficient mismatch repair (dMMR)/high levels of microsatellite instability (MSI-H) and proficient mismatch repair (pMMR), or non-high levels of microsatellite instability (non-MSI-H). PD-1/PD-L1 inhibitors have been proven to have favorable outcomes against dMMR/MSI-H CRC because of more T-cell infiltration into tumor tissues. Nevertheless, the effectiveness of PD-1/PD-L1 inhibitors in pMMR/non-MSI-H CRC is still uncertain. Because of the quite-lower proportion of dMMR/MSI-H in CRC, PD-1/PD-L1 inhibitors have been reported to combine with other antitumor treatments including chemotherapy, radiotherapy, and targeted therapy for better therapeutic effect in recent clinical trials. Neoadjuvant therapy, mainly including chemotherapy and radiotherapy, not only can reduce clinical stage but also benefit from local control, which can improve clinical symptoms and the quality of life. Adding immunotherapy into neoadjuvant therapy may change the treatment strategy of primary resectable or some metastatic CRC. In this review, we focus on the development of neoadjuvant anti-PD-1/PD-L1 therapy and discuss the future perspectives in CRC.